Development of a Sparse Direct Solver for Antenna Array Analysis - Sewraj, Keshav; Botha, Matthys M. (2021 International Conference on Electromagnetics in Advanced Applications (ICEAA), 2021)
Electromagnetic analysis of antenna arrays can be performed using the integral-equation based technique, the Method of Moments (MoM). However, the MoM is expensive is terms of computational time and memory requirement, hence restricted by the electrical size of the structure. Efficient MoM based techniques need to be developed to analyze large arrays. In this paper, a sparse direct solver for array analysis is explored. The MoM matrix equation is compressed using the single-level Directional Cross Approximation (DCA) technique. The DCA terms, together with MoM blocks for near interactions, are then used to create an extended sparse matrix to be solved directly. This is the first use of DCA in a direct solver scheme for electromagnetic field analysis, to the authors' knowledge. During the Gaussian elimination process of the sparse matrix, compressible fill-ins are redirected through existing paths in the graph of the matrix to preserve the sparsity of the matrix.